1988
DOI: 10.1136/pgmj.64.750.283
|View full text |Cite
|
Sign up to set email alerts
|

Improving laboratory usage: a review

Abstract: Summary:Influencing the ordering of laboratory investigations, and in particular reducing unnecessary ones, is a vital concern to many hospitals. An account of the reasons why control is necessary is presented. The different methods evaluated are reviewed, including rationing, form design, resource management (budget control), education, protocols and decision support systems, incentives, feedback and case note appraisal.Methods of controlling the requesting of investigations are likely to be ineffective unles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 34 publications
0
52
0
Order By: Relevance
“…Several systematic and narrative reviews have been published on this topic [5][6][7][8]. The most recent review, published in 1998, used a behavioral framework to classify interventions and found that targeting multiple behavioral factors was more successful than targeting a single factor [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic and narrative reviews have been published on this topic [5][6][7][8]. The most recent review, published in 1998, used a behavioral framework to classify interventions and found that targeting multiple behavioral factors was more successful than targeting a single factor [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, feedback about excessive ordering of 1 test, such as serum calcium, without comparative feedback, did not result in a significant reduction in ordering. 8 We hypothesized that physicians-in-training are not currently receiving feedback-especially not comparative feedback-on their resource utilization. Even if given, we hypothesized that this feedback was rarely used to implement an intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Diagnostic tests are often overused in modern medicine: one study found that "65% of laboratory tests, 11% of CXRs, and 26% of nursing services could not be justified" [29]. This may be a function of physicians' limited knowledge of diagnostic test cost.…”
Section: "Investigations"mentioning
confidence: 99%